Análise da eficiência na captação de radiação solar a partir de painéis solares fotovoltaicos na cidade de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Photovoltaic solar energy has been consolidated as a viable and sustainable alternative for generating electricity, especially in regions with a high incidence of solar radiation, where the use of this renewable source has been encouraged by its potential to reduce environmental impacts and dependence on fossil fuels. With this in mind, this work aims to analyze the validation of solar radiation capture from solar panels in the city of Santarém, PA, using sensor measurements and meteorological information, as well as making a comparison between the urban and rurais centers (UFOPA Experimental Farm). To this end, measurements were taken at two points along the study area, using photovoltaic panels and three pyranometers, two in the urban area and one in the rural area, enabling a comparison between the solar irradiance values and the energy production of the photovoltaic panels. The data analyzed showed a concomitance between photovoltaic production and the distribution of incoming solar radiation. The results show a strong correlation (r = 0.99) between solar irradiance and energy generation efficiency, demonstrating a direct relationship between the two variables. The analysis also showed that, despite the variations, solar energy can be highly productive, with the maximum average value recorded being 5479.15 W at 12:50 HL. In turn, irradiance differed between the areas analyzed, with the urban area having the highest incidence with a maximum average value of 728.19 W m-2 and the rural area 662.23 W m-2. The comparative analysis between the SP-LITE and ATMOS 41 equipment showed small discrepancies, highlighting differences in instrumental sensitivities, with SP-LITE being more sensitive. It can be concluded that the average instantaneous daily production of the photovoltaic system revealed that energy generation varies according to the incidence of solar radiation throughout the day, where it showed significant efficiency (>80%) even in conditions of lower irradiance. Despite the differences in instrumental sensitivities, both maintain consistency in the pattern of measured radiation variation. Finally, the results confirm the reliability of the measurements, reinforcing the predictability of solar irradiance based on photovoltaic production. Key
Keywords: Energia renovável; Painéis fotovoltaicos; Irradiância; CNPQ:: GEOCIÊNCIAS